The Role of Principal Leadership in Improving the Performance of PPPK Teachers at SDN 14 Bengkalis - Ria Sarlina; Zaka Hadikusuma Ramadan (Jurnal Kiprah Pendidikan, 2025)
This study aims to describe how the role of principal leadership in improving the performance of PPPK teachers. This study uses a qualitative approach in the form of a case study. The data sources for this study are the principal and 4 PPPK teachers as supporting informants. Data collection techniques and instruments in this case the researcher uses interview methods, observation and document review, focused data analysis using the Miles & Huberman model, namely data reduction, presentation, and drawing conclusions. There are four roles obtained, the first is the role of the principal as an educator, namely improving teacher professionalism, the ability to guide educational staff, implementing science and technology and providing good teaching examples, the second is the role of the principal as a supervisor, namely planning supervision, conducting class visits observing the learning process in the classroom, providing coaching and finding solutions to problems found and finding steps to improve teacher competence, the third is the role of the principal as an innovator, namely building positive relationships with the environment, finding new ideas and integrating activities, discipline and exemplary behavior, being adaptive and flexible, and the fourth is the role of the principal as a motivator, namely giving awards for achievements in teacher performance, empowering teachers through training and professional development, and creating open and supportive communication.